РОЛЬ ЭТНОКУЛЬТУРЫ В ВОСПИТАНИИ МОЛОДЕЖИ УЗБЕКИСТАНА В ДУХЕ НАЦИОНАЛЬНОЙ ИДЕОЛОГИИ (Conference Zone, 2022)
The article is dedicated to the development of young people, their understanding of national ideology and ethnocultural values. Describes the processes of a healthy lifestyle and the formation of a sense of respect for national and national values in order to avoid the emptiness of young people in the spiritual world. It also describes the state of youth policy and the problems of universal volues.